Bacillus Thuringiensis mutant increase activity against Apodoptera Frugiperda larvae - Cordeiro, J. X. [UNESP]; Laia, M. L.; Gonçalves, J. F. [UNESP]; Bergamasco, V. B. [UNESP]; Lemos, M. V F [UNESP] (My University, 2011)
Bacillus thuringiensis is a Gram-positive bacterium which main characteristic is the production of Cry proteins, that is toxic to some insects. These proteins, when ingested by susceptible insects, become active causing their death. In nature, it is possible to found B. thuringiensis strains which produce these proteins, but they differ in productivity (some of these isolates are more productive then others), and as to the toxicity levels of the produced proteins. Two B. thuringiensis strains that were highly effective against Spodoptera frugiperda larvae were chosen to verifying genetic mutation implication on Cry proteins productivity. One strain with a prolific spores production, while the other one only produced small amounts of spores. A genomic mutant library of these two isolates was, separately, constructed by genome Tn-5 transposon random insertion. Data analysis showed that mutation had a direct effect on the spores production, inducing an increase as well as a decrease in the production, according to the different strain observed. These results indicate, for the first time, that it is possible to use the described technique with B. thuringiensis, as well as the possibility to genetically breeding this bacteria. Another possibility introduced here is the possibility to do functional genetic studies mediated by mutagenesis in this bacterium.
Keywords: Cry genes; Functional genomics; Mutant library; Transposon